Economic evaluation of proton pump inhibitors in patients with gastro-oesophageal reflux disease: a systematic review - Aziz Rezapour; Sajad Moeini; Somayeh Afshari; Aghdas Souresrafil; Mohammad Barzegar; Seidamir Pasha Tabaeian (BMJ Open Gastroenterology)
Objectives Our aim was to systematically review the cost-effectiveness of proton pump inhibitor (PPI) therapies and surgical interventions for gastro-oesophageal reflux disease (GORD).Design The study design was a systematic review of economic evaluations.Data sources We searched PubMed, Embase, Scopus, and Web of Science for publications from January 1990 to March 2023. Only articles published in English were eligible for inclusion.Eligibility criteria Studies were included if they were full economic evaluations comparing PPIs with surgical or alternative therapies for GORD. Excluded were narrative reviews, non-peer-reviewed articles, and studies not reporting cost-effectiveness outcomes.Data extraction and synthesis Two reviewers independently extracted data on study design, comparators, time horizon, and cost-effectiveness outcomes. The quality of studies was assessed using the Joanna Briggs Institute (JBI) checklist for economic evaluations.Results A total of 25 studies met the inclusion criteria. Laparoscopic Nissen fundoplication (LNF) was found to be cost-effective in long-term horizons, while PPIs were preferred for short- to medium-term outcomes. Differences in healthcare settings and methodological approaches influenced the study findings.Conclusions Strategic purchasing decisions for GORD treatment should consider the time horizon, healthcare setting, and cost structures. LNF may provide better long-term value, but PPIs remain effective for managing symptoms in the short term.Study registration PROSPERO, CRD42023474181.